Entrainment of the circadian rhythm in the rat pineal N-acetyltransferase activity by melatonin is photoperiod dependent - Humlová, M; Illnerová, H (Journal of pineal research, 1992)
Entraining effect of melatonin on the circadian rhythm in rat pineal N-acetyltransferase (NAT) activity was studied under various photoperiods. Melatonin administration prior to dark onset for 5 successive days phase-advanced the evening NAT rise under the light:dark (LD) cycle of either LD 10:14 or LD 8:16, but not under LD 12:12. It is assumed that under the latter regime, the end of a light period exhibited a phase-delaying effect on the NAT rise. The light exposure appeared to be a stronger Zeitgeber than melatonin itself. Data show that melatonin applied in the late light period advances the evening NAT rise under a short photoperiod only; under a longer photoperiod, the phase-advancing effect of melatonin may conflict with a phase-delaying effect of the end of a light period, and the effect of light exposure overrides that of melatonin.
Keywords: Circadian Rhythm; Arylamine N-Acetyltransferase; Rats; Photoperiod; pohybová aktivita; fotoperioda; cirkadiánní rytmus; Rats, Wistar; mužské pohlaví; epifýza mozková; krysa rodu Rattus; Pineal Gland; zvířata; Melatonin; melatonin; potkani Wistar; Motor Activity; arylamin-N-acetyltransferasa; Male; Animals